2022
DOI: 10.3389/fneur.2022.997217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating children with vestibular migraine through vestibular test battery: A cross-sectional investigation

Abstract: ObjectiveThe present study aimed to investigate the status of vestibular function in children with vestibular migraine of childhood (VMC) reflected by vestibular function test battery and explore the pathophysiological implication of these instrument-based findings.MethodsThe clinical data of 22 children (mean age 10.7 ± 2.9 years) with VMC who met the diagnostic criteria of the Barany Society were collected from September 2021 to March 2022. A vestibular function test battery on these children included a calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
1
1
Order By: Relevance
“…The age of onset of vertigo in our sample of VMC was 15.6 years (range 11-17), which is later than onset of probable VMC and RVC, although another study reported that the age of onset was 10.7 years in a sample of 22 subjects (16). Our data are not different from those of other investigations reporting the onset of vertigo in a sample of subjects around 14 years in which comorbidity for migraine was not assessed (17).…”
Section: Discussioncontrasting
confidence: 77%
“…The age of onset of vertigo in our sample of VMC was 15.6 years (range 11-17), which is later than onset of probable VMC and RVC, although another study reported that the age of onset was 10.7 years in a sample of 22 subjects (16). Our data are not different from those of other investigations reporting the onset of vertigo in a sample of subjects around 14 years in which comorbidity for migraine was not assessed (17).…”
Section: Discussioncontrasting
confidence: 77%
“…En un estudio retrospectivo realizado en niños diagnosticados de migraña vestibular, migraña vestibular probable y vértigo recurrente de la infancia según los criterios de la Sociedad Bárány, tanto la tomografía computarizada cerebral como el vHIT, no demostraron ningún hallazgo relevante en estos pacientes [20]. Zhang et al en 2022, no encontraron diferencias significativas en los resultados de pruebas vestibulares (pruebas calóricas, vHIT y VEMP) en niños diagnosticados de migraña vestibular de forma exclusiva [21]. En otro estudio de niños diagnosticados con migraña vestibular o sus equivalentes, no se encontraron diferencias en parámetros audiométricos ni vestibulares evaluados [22].…”
Section: Criterios Diagnósticosunclassified
“…A recent study examined age-related characteristics in the onset of vestibular migraines and discovered that external spontaneous vertigo and visually-induced vertigo are distinguishing clinical features of juvenile forms (45). Another study investigating vestibular migraine in children revealed high rates of abnormalities in vestibular test, suggesting the involvement of the lateral semicircular canal, the utricle, and the superior vestibular conduction pathway in vestibular migraine of childhood (46), indicating peripheral vestibular dysfunction may contribute to the manifestation of vestibular symptoms.…”
Section: Tinnitus and Dizziness In Early Onset Migrainementioning
confidence: 99%